Saccharomyces cerevisiae Induces Immune Enhancing and Shapes Gut Microbiota in Social Wasps - Meriggi, Niccolò; Di Paola, Monica; Vitali, Francesco; Rivero, Damariz; Cappa, Federico; Turillazzi, Francesco; Gori, Agnese; Dapporto, Leonardo; Beani, Laura; Turillazzi, Stefano; Cavalieri, Duccio (Frontiers in Microbiology, 2019)
Trained immunity is the enhanced response of the innate immune system to a secondary infection after an initial encounter with a microorganism. This non-specific response to reinfection is a primitive form of adaptation that has been shown to be conserved from plants to mammals. Insects lack an acquired immune component and rely solely on an innate one, and they have expanded it upon traits of plasticity and adaptation against pathogens in the form of immune priming. The recent discoveries of the role of Saccharomyces cerevisiae in the insect’s ecology and the ability of this yeast to induce trained immunity in different organisms suggest that insects could have developed mechanisms of adaptation and immune enhancing. Here, we report that two yeast strains of S. cerevisiae, previously shown to induce trained immunity in mammals, enhance resistance to Escherichia coli infection in the paper wasp Polistes dominula. The reduction of injected E. coli load by S. cerevisiae strains was statistically significant in future foundresses but not in workers, and this occurs before and after hibernation. We thus investigated if the effect on E. coli was mirrored by variation in the gut microbiota composition. Foundresses, showing immune enhancing, had statistically significant changes in composition and diversity of gut bacterial communities but not in the fungal communities. Our results demonstrate that S. cerevisiae can prime insect responses against bacterial infections, providing an advantage to future foundress wasps to carry these microorganisms. Understanding the mechanisms involved in the generation of specific and long-lasting immune response against pathogenic infections in insects and the influence of the induction of trained immunity on the commensal gut microbiota could have a major impact on modern immunology.